1988
DOI: 10.1080/09553008814551121
|View full text |Cite
|
Sign up to set email alerts
|

An ESR Investigation of the Reactions of Glutathione, Cysteine and Penicillamine Thiyl Radicals: Competitive Formation of RSO·, R·, RSSR, and RSS·

Abstract: The reactions of the cysteine, glutathione and penicillamine thiyl radicals with oxygen and their parent thiols in frozen aqueous solutions have been elucidated through electron spin resonance spectroscopy. The major sulfur radicals observed are: (1) thiyl radicals, RS.; (2) disulfide radical anions. RSSR-.; (3) perthiyl radicals, RSS. and upon introduction of oxygen; (4) sulfinyl radicals, RSO., where R represents the remainder of the cysteine, glutathione or penicillamine moiety. The radical product observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 34 publications
2
34
0
Order By: Relevance
“…1 An important feature of tryptophan photolysis is the potential for photoinduced electron transfer to nearby disulfide bridges 1 where disulfide reduction leads to a thiolate and a thiyl radical. 1 Thiyl radicals can form also via direct light-induced homolysis of cystine disulfide bonds [29][30][31][32] and a number of reaction products have been characterized for thiyl radical pairs generated in such way 1, [33][34][35][36][37] For completeness, we note that disulfide bonds can also cleave via C-S bond breakage into carbon-centered radicals and perthiyl radicals, but this process appears to prevail for β-alkyl substituted disulfides such as, for example, penicillamine. 30 For comparison, the light-induced cleavage of glutathione disulfide led predominantly to thiyl radicals.…”
Section: Chemistry Of Photooxidationmentioning
confidence: 99%
“…1 An important feature of tryptophan photolysis is the potential for photoinduced electron transfer to nearby disulfide bridges 1 where disulfide reduction leads to a thiolate and a thiyl radical. 1 Thiyl radicals can form also via direct light-induced homolysis of cystine disulfide bonds [29][30][31][32] and a number of reaction products have been characterized for thiyl radical pairs generated in such way 1, [33][34][35][36][37] For completeness, we note that disulfide bonds can also cleave via C-S bond breakage into carbon-centered radicals and perthiyl radicals, but this process appears to prevail for β-alkyl substituted disulfides such as, for example, penicillamine. 30 For comparison, the light-induced cleavage of glutathione disulfide led predominantly to thiyl radicals.…”
Section: Chemistry Of Photooxidationmentioning
confidence: 99%
“…1989) . The perthiyl radical RSS' may also be formed directly by interaction of RS' with RSH (Becker et al 1988) . Furthermore, the addition-elimination reactions (17/17'), followed by (18),…”
Section: Discussionmentioning
confidence: 98%
“…Reaction (19) ated frozen systems (Becker et al 1988), but the radiation chemistry of these systems at ambient temperature is not well understood . It might be suggested that RSS -also interacts catalytically with 0 2 to form 02' -radicals, which could then reduce Fe(iiz)cytc (Butler et al 1982) .…”
Section: Discussionmentioning
confidence: 99%
“…ESR experiments following the generation of thiyl radicals from Cys, 25 GSH, 26 and penicillamine (PenSH) 26 have also indicated the formation of carbon-centered radicals, and especially the presence of more than one carbon-centered radical after the oxidation of GSH 26 points to the fact that the γ-Glu C α –H bond is not the only hydrogen donor for intra molecular hydrogen transfer to the original thiyl radical. In fact, Becker et al 27 had suggested the formation of a carbon-centered radical at the C α position of Cys upon γ-irradiation of GSH in water ice at pH 3, i.e. under conditions where the N-terminal amino group of the γ-Glu residue is protonated and would not permit the formation of a capto-datively 28 stabilized radical at the C α position of γ-Glu.…”
Section: Introductionmentioning
confidence: 99%